Acute myeloid leukemia with NUP98::RARG resembling acute promyelocytic leukemia accompanying ARID1B gene mutation - Wu, Danyang; Gao, Ran (Hematology (Luxembourg), 2023)
In this study, we present a case of acute myeloid leukemia characterized by the t(11;12)(p15;q13) translocation, exhibiting clinical, immunophenotypical, and morphological features consistent with acute promyelocytic leukemia (APL). The RNA sequencing analysis of the patient's bone marrow samples revealed the presence of the NUP98-retinoic acid receptor gamma (RARG) (NUP98::RARG) gene resulting from the translocation. Furthermore, the presence of a mutation in the ARID1B gene in the patient under study indicates a potential association with resistance to all-trans retinoic acid (ATRA).